Methane catalytic combustion catalyst and preparation method thereof

Through the preparation of TiO2@ABO3 core-shell catalyst, the problem of insufficient low-temperature activity of perovskite catalysts is solved, and a high-efficiency and low-cost methane catalytic combustion effect is achieved.

CN119236951AActive Publication Date: 2025-01-03CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310790363.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2025-01-03
Estimated Expiration
2043-06-30

AI Technical Summary

Technical Problem

The existing perovskite methane catalytic combustion catalysts have poor catalytic activity at low temperatures, and high-temperature calcination during the preparation process leads to a small specific surface area, which affects the stability and efficiency of the catalyst.

Method used

TiO2@ABO3 core-shell catalyst is used to disperse TiO2, hydroxysulfopropyl betaine and active metal salt solution by ultrasonic to form a structure with perovskite metal oxide as the shell layer and TiO2 as the core, and roast it at a suitable temperature. , optimize the low-temperature activity and stability of the catalyst.

Benefits of technology

The low-temperature catalytic activity and stability of the catalyst are improved, T90≤500℃, and methane is efficiently removed under low temperature conditions, and the cost is low.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a methane catalytic combustion catalyst and a preparation method thereof.The preparation method comprises the steps that 1, TiO2 is ultrasonically dispersed in absolute ethyl alcohol, hydroxysulfopropyl betaine is added, and a mixture is prepared; (2) uniformly mixing the mixture in the step (1) and an active metal salt solution for reaction; and (3) after the reaction, separating out a precipitate, and drying and roasting to obtain the TiO2 (at) ABO3 core-shell catalyst. The perovskite core-shell catalyst provided by the invention is used for catalytic combustion of methane, T90 is less than or equal to 500 DEG C, and the perovskite core-shell catalyst has the advantages of high low-temperature catalytic activity, good stability, low cost and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of waste gas treatment, and specifically relates to a methane catalytic combustion catalyst and a preparation method thereof. Background Art

[0002] Methane is the second largest greenhouse gas, accounting for about 20% of global greenhouse gas emissions and contributing about a quarter to global warming. Methane molecules are stable tetrahedral structures and can be decomposed at high temperatures above 1500°C. Methane catalytic combustion technology is an effective means of methane control that can effectively replace traditional thermal combustion methods. The key lies in the catalyst. There are roughly two types of methane catalytic combustion catalysts: precious metal catalysts and non-precious metal catalysts. Among them, although precious metal catalysts have good low-temperature ignition activity and anti-poisoning ability, their large-scale production and application are subject to certain constraints due to factors such as poor high-temperature stability and high cost of precious metals. Non-precious metal catalysts are mainly divided into perovskite-type metal composite oxides and hexaaluminate-type metal composite oxides (the disadvantage is that the product preparation is relatively difficult) and other metal oxides (the disadvantage is that it is easy to sinter at high temperatures). Perovskite-type catalysts can overcome the above disadvantages and have the characteristics of moderate ignition temperature, simple and easy preparation process, low cost, and strong resistance to high-temperature sintering, but poor low-temperature activity limits their development and application.

[0003] CN106944093A discloses a perovskite-type honeycomb monolithic methane catalytic combustion catalyst and a preparation method thereof, wherein the catalyst comprises an active component and an inert honeycomb carrier, wherein the active component comprises rare earth metal elements, alkaline earth metal elements, and transition metal elements, and the carrier is a cordierite-based honeycomb carrier, a mullite-based honeycomb carrier, or an alumina-based honeycomb carrier. The preparation method comprises the following steps: (1) Preparation of an active component precursor solution: preparing an aqueous solution of a soluble metal salt according to the molar ratio of the metal elements required by the active component, i.e., an active component precursor solution, wherein the total molar concentration of metal ions is 1.0-2.0 mol / L; (2) Loading of the active component: impregnating the inert honeycomb carrier with the active component precursor solution, and drying and calcining the inert honeycomb carrier after impregnation to obtain the perovskite-type honeycomb monolithic methane catalytic combustion catalyst. The calcination temperature is 750-850°C and the time is 2-3h. At an air velocity of 15000h -1 Under the conditions of CH43.0% (v / v), T 10 >500℃,T 90 >650℃, low temperature catalytic activity needs to be improved.

[0004] CN112691702A discloses a perovskite-type methane combustion catalyst and its preparation method and application. The perovskite-type methane combustion catalyst includes an active component and a carrier, the carrier carries the active component, the carrier includes titanium silicon molecular sieve, the screening of Bacillus cereus and its hydrogen production performance, the active component is LaSrCo x Ni 1-x TiO6, titanium silicon molecular sieve provides titanium element for the active component, and the titanium silicon molecular sieve loads the active component through titanium oxygen bond, where x is 0.4-0.7; the specific surface area of ​​the catalyst is 200m 2 / g-280m 2 / g. The preparation steps are as follows: first, the titanium silicon molecular sieve is immersed in an alkaline solution to obtain a modified titanium silicon molecular sieve, then the modified titanium silicon molecular sieve is added to a metal salt aqueous solution, and citric acid is added to mix, after heating, a precipitant is added for aging, and a catalyst semi-finished product is obtained by roasting, and then the catalyst semi-finished product, alumina, a binder and an extrusion aid are extruded into a mold, and the catalyst is obtained after calcination; the metal salt in the metal salt aqueous solution includes lanthanum salt, strontium salt, cobalt salt and nickel salt. The catalyst can convert 10% of methane below 450°C and reaches the ignition temperature. However, the final conversion temperature for converting 90% of methane is around 625°C, and the low-temperature catalytic activity needs to be improved.

[0005] In recent years, core-shell structure materials have been widely used in the research and development of catalytic materials due to their advantages such as controllable size, regular shape, and better catalytic effect and catalytic stability than general supported catalysts.

[0006] CN105562122A discloses a metal oxide with a perovskite core-shell structure, which has the advantages of large specific surface area, uniform particle size and good stability. The general formula of the metal oxide is ABO3, A is a rare earth element, B is a transition metal element, and the metal oxide has the oxide of A as the core and the oxide of B as the shell. The catalyst is prepared by a hydrothermal method, comprising the following steps: (1) dissolving the salt of A and the salt of B in water according to the stoichiometric ratio of A and B in the general formula ABO3, adding a surfactant, stirring evenly or until transparent, and obtaining a mixed solution; (2) transferring the mixed solution obtained in step (1) to a high-pressure reactor, heating for hydrothermal reaction, centrifugation and washing after the reaction is completed, and obtaining a precipitate; (3) drying and roasting the precipitate obtained in step (2) to obtain the metal oxide with a perovskite core-shell structure. It is applied to a variety of catalytic reactions, such as hydrocarbon catalytic oxidation, CO oxidation and photocatalysis. However, the catalyst is obtained by high-temperature roasting to obtain the final catalyst during the preparation process, which easily leads to a lower specific surface area, thereby affecting the low-temperature catalytic activity of the catalyst. Summary of the invention

[0007] In view of the shortcomings of the prior art, the present invention provides a catalyst for catalytic combustion of methane and a preparation method thereof. The perovskite core-shell catalyst provided by the present invention is used for catalytic combustion of methane. 90 ≤500℃, it has the advantages of high low-temperature catalytic activity, good stability and low cost.

[0008] The method for preparing a methane catalytic combustion catalyst provided by the present invention comprises the following steps:

[0009] (1) ultrasonically dispersing TiO2 in anhydrous ethanol, adding hydroxysulfopropyl betaine to prepare a mixture;

[0010] (2) mixing the mixture of step (1) and the active metal salt solution for reaction;

[0011] (3) After the reaction, the precipitate is separated, dried and calcined to obtain the TiO2@ABO3 core-shell catalyst.

[0012] In the present invention, the TiO2 described in step (1) is preferably rutile type with a particle size of 40 to 60 nm.

[0013] In the present invention, the mass volume ratio of TiO2 and anhydrous ethanol in step (1) is 1g:10-30mL, preferably 1g:10-20mL.

[0014] In the present invention, the frequency of the ultrasonic dispersion in step (1) is 2 to 4 kHz, and the ultrasonic time is 10 to 30 minutes.

[0015] In the present invention, the mass ratio of hydroxysulfopropyl betaine added in step (1) to TiO2 is 1:5 to 20, preferably 1:10 to 15. After the addition, ultrasonic treatment is continued at 2 to 4 KHz for 30 to 60 minutes.

[0016] In the present invention, the active metal described in step (2) is a non-precious metal, specifically including two kinds of metals A and B, wherein A is generally at least one of La, Ce, etc., and B is generally at least one of Fe, Co, Ni, Mn, etc., wherein the molar ratio of active metals A and B is 1:1. The active metal salt solution is generally a soluble metal salt thereof, such as one or more of nitrates, chlorides, etc., and the concentration of the active metal salt solution is generally 1 to 3 mol / L.

[0017] In the present invention, further, in step (2), hydroquinone is added to the active metal salt solution, and the mass concentration of hydroquinone in the solution after the addition is 3% to 5%.

[0018] In the present invention, the active metal salt solution is mixed with the mixture of step (1) according to the molar ratio of TiO2 to active metal of 1:1 to 5. After mixing, the mixture is stirred at 40 to 70°C for 1 to 3 hours at a stirring rate of 200 to 500 r / min.

[0019] In the present invention, step (3) separates the precipitate by conventional solid-liquid separation, preferably by centrifugal separation.

[0020] In the present invention, the drying temperature in step (3) is 80 to 120° C., and the drying time is 12 to 24 hours.

[0021] In the present invention, the calcination temperature in step (3) is 700-800° C. and the calcination time is 4-6 hours.

[0022] The methane catalytic combustion catalyst of the present invention is prepared by the above-mentioned method of the present invention. The prepared catalyst is a TiO2@ABO3 catalyst with a perovskite metal oxide (ABO3) as a shell and TiO2 as a core, and the thickness of the ABO3 shell is 5 to 35 nm.

[0023] The present invention also provides application of the prepared methane catalytic combustion catalyst, which is used for catalytic combustion of methane at low temperature and has the advantages of high low-temperature catalytic activity, good stability and the like.

[0024] In the application of the present invention, at a volume space velocity of 10000h -1 ~30000h -1 , under the condition of methane volume concentration of 1% to 3%, T 90 ≤500℃.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] (1) The inventors of the present application have found in their research that high-temperature calcination during the preparation of perovskite-type catalysts can easily lead to high crystallinity and small specific surface area, resulting in poor low-temperature catalytic activity. On this basis, the inventors of the present application introduced hydroxysulfopropyl betaine during the catalyst preparation process to prepare a core-shell catalyst with TiO2 as the core and perovskite metal oxide as the shell, wherein the TiO2 carrier has an electrically neutral and stable structure, and the charged hydroxysulfopropyl betaine and metal salt are easily evenly dispersed around it, forming a stable core-shell structure during the interaction of the three, which has excellent low-temperature activity and stability.

[0027] (2) Hydroxysulfopropyl betaine is introduced during the catalyst preparation process. The cation at position A can combine with the hydroxyl anion group of hydroxysulfopropyl betaine, and the sulfonic acid anion interacts with the metal at position B, which can effectively connect the carrier and the active metal to form a uniform and stable core-shell structure. In addition, the electronegativity of N and S in hydroxysulfopropyl betaine is strong, which has an electron-withdrawing induction effect, can optimize the arrangement of metal oxides, and help maintain the stability of the core-shell structure.

[0028] (3) Introducing hydroquinone into the active metal salt solution. Hydroquinone has a para-hydroxy structure and works together with hydroxysulfopropyl betaine to not only increase the metal cation concentration on the TiO2 surface, but also help maintain the stability of the core-shell structure. DETAILED DESCRIPTION

[0029] The technical solution of the present invention and its effects are further illustrated by the following examples. The examples are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and specific operation processes are given, but the protection scope of the present invention is not limited to the following examples.

[0030] The experimental methods in the following examples, unless otherwise specified, are all conventional methods in the art. The experimental materials used in the following examples, unless otherwise specified, can all be purchased from biochemical reagent stores.

[0031] In the embodiment of the present invention, T 10 Indicates the methane ignition temperature when the methane conversion rate reaches 10%, T 90 Indicates the methane ignition temperature when the methane conversion rate reaches 90%.

[0032] Example 1

[0033] (1) 5 g of 40 nm rutile TiO2 was ultrasonically dispersed in 75 mL of anhydrous ethanol at a frequency of 2 kHz for 15 min, 0.375 g of hydroxysulfopropyl betaine was added, and the mixture was ultrasonically dispersed at a frequency of 2 kHz for 30 min to obtain a mixture;

[0034] (2) preparing an active metal salt solution with a concentration of 2.5 mol / L, wherein metal salt A is La(NO3)3·6H2O, and metal salts B are Fe(NO3)3·9H2O and Ni(NO3)2·6H2O, wherein the molar ratio of A to B is 1:1, and the molar ratio of Ni to Fe is 0.2:0.8; mixing the mixture with the active metal salt solution according to a molar ratio of TiO2 to active metal of 1:4, stirring at 60°C for 2.5 hours, and the stirring speed is 300 r / min.

[0035] (3) After the reaction, the precipitate was separated by centrifugation, dried at 100°C for 12 hours, and calcined at 750°C for 4 hours to obtain TiO2@LaNi 0.2 Fe 0.8 O3 core-shell catalyst, wherein the shell thickness is 23-27nm.

[0036] The activity evaluation results of the prepared catalyst are as follows:

[0037] At a methane volume concentration of 1% and a volume space velocity of 30,000 h -1 Under the condition, T 90 The methane removal rate was 88.7% after continuous operation at 465°C for 100 hours.

[0038] At a methane volume concentration of 3% and a volume space velocity of 10000 h -1 Under the condition, T 90 The temperature is 458℃, and the methane removal efficiency is 86.9% after continuous operation at 458℃ for 100 hours.

[0039] Example 2

[0040] (1) 10 g of 40 nm rutile TiO2 was ultrasonically dispersed in 100 mL of anhydrous ethanol at a frequency of 2 kHz for 10 min, 1 g of hydroxysulfopropyl betaine was added, and the mixture was ultrasonically dispersed at a frequency of 2 kHz for 60 min to obtain a mixture;

[0041] (2) preparing an active metal salt solution with a concentration of 2.5 mol / L, wherein metal salt A is La(NO3)3·6H2O, and metal salts B are Fe(NO3)3·9H2O and Ni(NO3)2·6H2O, wherein the molar ratio of A to B is 1:1, and the molar ratio of Ni to Fe is 0.2:0.8; mixing the mixture with the active metal salt solution in a molar ratio of TiO2 to active metal of 1:1, stirring at 70°C for 2.5 hours, and the stirring speed is 300 r / min.

[0042] (3) After the reaction, the precipitate was separated by centrifugation, dried at 80°C for 24 hours, and calcined at 800°C for 4 hours to obtain TiO2@LaNi 0.2 Fe 0.8 O3 core-shell catalyst, wherein the shell thickness is 25-29nm.

[0043] The activity evaluation results of the prepared catalyst are as follows:

[0044] At a methane volume concentration of 1% and a volume space velocity of 30,000 h -1 Under the condition, T 90 The methane removal rate was 87.7% after continuous operation at 466°C for 100 hours.

[0045] At a methane volume concentration of 3% and a volume space velocity of 10000 h -1 Under the condition, T 90 The temperature is 462℃, and the methane removal efficiency is 85.3% after continuous operation at 462℃ for 100 hours.

[0046] Example 3

[0047] (1) 4 g of 60 nm rutile TiO2 was ultrasonically dispersed in 80 mL of anhydrous ethanol at a frequency of 3 kHz for 30 min, 0.3 g of hydroxysulfopropyl betaine was added, and the mixture was ultrasonically dispersed at a frequency of 2 kHz for 30 min to obtain a mixture;

[0048] (2) preparing an active metal salt solution with a concentration of 3.0 mol / L, wherein metal salt A is La(NO3)3·6H2O, and metal salts B are Fe(NO3)3·9H2O and Ni(NO3)2·6H2O, wherein the molar ratio of A to B is 1:1, and the molar ratio of Ni to Fe is 0.2:0.8; mixing the mixture with the active metal salt solution at a molar ratio of TiO2 to active metal of 1:5, stirring the reaction at 70°C for 2.5 hours, and the stirring speed is 300 r / min.

[0049] (3) After the reaction, the precipitate was separated by centrifugation, dried at 120°C for 12 hours, and calcined at 800°C for 4 hours to obtain TiO2@LaNi 0.2 Fe 0.8 O3 core-shell catalyst, wherein the shell thickness is 22-27nm.

[0050] The activity evaluation results of the prepared catalyst are as follows:

[0051] At a methane volume concentration of 1% and a volume space velocity of 30,000 h -1 Under the condition, T 90 The methane removal rate was 88.3% after continuous operation at 470°C for 100 hours.

[0052] At a methane volume concentration of 3% and a volume space velocity of 10000 h -1 Under the condition, T 90 The temperature is 467℃, and the methane removal efficiency is 87.1% after continuous operation at 467℃ for 100 hours.

[0053] Example 4

[0054] (1) 5 g of 40 nm rutile TiO2 was ultrasonically dispersed in 75 mL of anhydrous ethanol at a frequency of 2 kHz for 15 min, 0.375 g of hydroxysulfopropyl betaine was added, and the mixture was ultrasonically dispersed at a frequency of 2 kHz for 30 min to obtain a mixture;

[0055] (2) preparing an active metal salt solution with a concentration of 2.5 mol / L, wherein metal salt A is Ce(NO3)3·6H2O, and metal salts B are Fe(NO3)3·9H2O and Ni(NO3)2·6H2O, wherein the molar ratio of A to B is 1:1, and the molar ratio of Ni to Fe is 0.2:0.8; mixing the mixture with the active metal salt solution according to a molar ratio of TiO2 to active metal of 1:4, stirring the reaction at 60°C for 2.5 hours, and the stirring speed is 300 r / min.

[0056] (3) After the reaction, the precipitate was separated by centrifugation, dried at 100 °C for 12 hours, and calcined at 750 °C for 4 hours to obtain TiO2@CeNi 0.2 Fe 0.8 O3 core-shell catalyst, wherein the shell thickness is 28-33nm.

[0057] The activity evaluation results of the prepared catalyst are as follows:

[0058] At a methane volume concentration of 1% and a volume space velocity of 30,000 h -1 Under the condition, T 90 The temperature was 464°C. The methane removal rate was 88.0% after continuous operation at 464°C for 100 hours.

[0059] At a methane volume concentration of 3% and a volume space velocity of 10000 h -1 Under the condition, T 90 The temperature is 458℃, and the methane removal efficiency is 86.6% after continuous operation at 458℃ for 100 hours.

[0060] Example 5

[0061] (1) 5 g of 40 nm rutile TiO2 was ultrasonically dispersed in 75 mL of anhydrous ethanol at a frequency of 2 kHz for 15 min, 0.375 g of hydroxysulfopropyl betaine was added, and the mixture was ultrasonically dispersed at a frequency of 2 kHz for 30 min to obtain a mixture;

[0062] (2) preparing an active metal salt solution with a concentration of 2.5 mol / L, wherein metal salt A is La(NO3)3·6H2O, and metal salts B are Mn(NO3)2·6H2O and Co(NO3)2·6H2O, wherein the molar ratio of A to B is 1:1, and the molar ratio of Co to Mn is 0.2:0.8; mixing the mixture with the active metal salt solution according to a molar ratio of TiO2 to active metal of 1:4, stirring at 60°C for 2.5 hours, and the stirring speed is 300 r / min.

[0063] (3) After the reaction, the precipitate was separated by centrifugation, dried at 100 °C for 12 hours, and calcined at 750 °C for 4 hours to obtain TiO2@LaCo0.2 Mn 0.8 O3 core-shell catalyst, wherein the shell thickness is 24-27nm.

[0064] The activity evaluation results of the prepared catalyst are as follows:

[0065] At a methane volume concentration of 1% and a volume space velocity of 30,000 h -1 Under the condition, T 90 The methane removal rate was 89.0% after continuous operation at 478°C for 100 hours.

[0066] At a methane volume concentration of 3% and a volume space velocity of 10000 h -1 Under the condition, T 90 The temperature is 474℃, and the methane removal efficiency is 87.5% after continuous operation at 474℃ for 100 hours.

[0067] Example 6

[0068] (1) 5 g of 40 nm rutile TiO2 was ultrasonically dispersed in 75 mL of anhydrous ethanol at a frequency of 2 kHz for 15 min, 0.375 g of hydroxysulfopropyl betaine was added, and the mixture was ultrasonically dispersed at a frequency of 2 kHz for 30 min to obtain a mixture;

[0069] (2) preparing an active metal salt solution with a concentration of 2.5 mol / L, wherein metal salt A is La(NO3)3·6H2O, and metal salts B are Fe(NO3)3·9H2O and Ni(NO3)2·6H2O, wherein the molar ratio of A to B is 1:1, and the molar ratio of Ni to Fe is 0.2:0.8; adding hydroquinone to the active metal salt solution, wherein the mass concentration of hydroquinone in the solution after addition is 3.39%; mixing the mixture and the active metal salt solution according to a molar ratio of TiO2 to active metal of 1:4, stirring at 60°C for 2.5 hours, and the stirring speed is 300 r / min.

[0070] (3) After the reaction, the precipitate was separated by centrifugation, dried at 100°C for 12 hours, and calcined at 750°C for 4 hours to obtain TiO2@LaNi 0.2 Fe 0.8 O3 core-shell catalyst, wherein the shell thickness is 26-29nm.

[0071] The activity evaluation results of the prepared catalyst are as follows:

[0072] At a methane volume concentration of 1% and a volume space velocity of 30,000 h -1 Under the condition, T 90 The methane removal rate was 89.1% after continuous operation at 453°C for 100 hours.

[0073] At a methane volume concentration of 3% and a volume space velocity of 10000 h -1 Under the condition, T 90 The temperature is 450℃, and the methane removal efficiency is 88.5% after continuous operation at 450℃ for 100 hours.

[0074] Example 7

[0075] (1) 5 g of 40 nm rutile TiO2 was ultrasonically dispersed in 75 mL of anhydrous ethanol at a frequency of 2 kHz for 15 min, 0.375 g of hydroxysulfopropyl betaine was added, and the mixture was ultrasonically dispersed at a frequency of 2 kHz for 30 min to obtain a mixture;

[0076] (2) preparing an active metal salt solution with a concentration of 2.5 mol / L, wherein metal salt A is La(NO3)3·6H2O, and metal salts B are Mn(NO3)2·6H2O and Co(NO3)2·6H2O, wherein the molar ratio of A to B is 1:1, and the molar ratio of Co to Mn is 0.2:0.8; adding hydroquinone to the active metal salt solution, wherein the mass concentration of hydroquinone in the solution after addition is 5.0%; mixing the mixture and the active metal salt solution according to a molar ratio of TiO2 to active metal of 1:4, stirring at 60°C for 2.5 hours, and the stirring speed is 300 r / min.

[0077] (3) After the reaction, the precipitate was separated by centrifugation, dried at 100 °C for 12 hours, and calcined at 750 °C for 4 hours to obtain TiO2@LaCo 0.2 Mn 0.8 O3 core-shell catalyst, wherein the shell thickness is 24-28nm.

[0078] The activity evaluation results of the prepared catalyst are as follows:

[0079] At a methane volume concentration of 1% and a volume space velocity of 30,000 h -1 Under the condition, T 90 The methane removal rate was 89.2% after continuous operation at 469°C for 100 hours.

[0080] At a methane volume concentration of 3% and a volume space velocity of 10000 h -1 Under the condition, T 90 The temperature is 463℃, and the methane removal efficiency is 89.3% after continuous operation at 463℃ for 100 hours.

[0081] Example 8

[0082] (1) 5 g of 40 nm rutile TiO2 was ultrasonically dispersed in 75 mL of anhydrous ethanol at a frequency of 2 kHz for 15 min, 0.375 g of hydroxysulfopropyl betaine was added, and the mixture was ultrasonically dispersed at a frequency of 2 kHz for 30 min to obtain a mixture;

[0083] (2) preparing an active metal salt solution with a concentration of 2.5 mol / L, wherein metal salt A is La(NO3)3·6H2O, and metal salt B is Fe(NO3)3·9H2O, wherein the molar ratio of A to B is 1:1; adding hydroquinone to the active metal salt solution, wherein the mass concentration of hydroquinone in the solution after addition is 3.39%; mixing the mixture and the active metal salt solution according to a molar ratio of TiO2 to active metal of 1:4, stirring at 60°C for 2.5 hours, and the stirring speed is 300 r / min.

[0084] (3) After the reaction, the precipitate was separated by centrifugation, dried at 100°C for 12 hours, and calcined at 750°C for 4 hours to obtain TiO2@LaNi 0.2 Fe 0.8 O3 core-shell catalyst, wherein the shell thickness is 25-30nm.

[0085] The activity evaluation results of the prepared catalyst are as follows:

[0086] At a methane volume concentration of 1% and a volume space velocity of 30,000 h -1 Under the condition, T 90 The temperature was 459°C. The methane removal rate was 88.9% after continuous operation at 459°C for 100 hours.

[0087] At a methane volume concentration of 3% and a volume space velocity of 10000 h -1 Under the condition, T 90 The temperature is 457℃, and the methane removal efficiency is 88.8% after continuous operation at 457℃ for 100 hours.

[0088] Comparative Example 1

[0089] The same as Example 1, except that: hydroxysulfopropyl betaine was not added in step (1), and the catalyst finally obtained did not form a core-shell structure. The activity evaluation results of the prepared catalyst are as follows:

[0090] At a methane volume concentration of 1% and a volume space velocity of 30,000 h -1 Under the condition, T 90 The methane removal rate was 88.2% after continuous operation at 570°C for 100 hours.

[0091] At a methane volume concentration of 1% and a volume space velocity of 30,000 h -1 Under the condition, T 90The temperature was 562°C. The methane removal rate was 87.8% after continuous operation at 562°C for 100 hours.

[0092] Comparative Example 2

[0093] The same as Example 1, except that: in step (1), alkylamido betaine is used instead of hydroxysulfopropyl betaine, and the catalyst finally obtained does not form a core-shell structure. The activity evaluation results of the prepared catalyst are as follows:

[0094] At a methane volume concentration of 1% and a volume space velocity of 30,000 h -1 Under the condition, T 90 The methane removal rate was 88.4% after continuous operation at 569°C for 100 hours.

[0095] At a methane volume concentration of 3% and a volume space velocity of 10000 h -1 Under the condition, T 90 The temperature is 558℃, and the methane removal efficiency is 86.7% after continuous operation at 558℃ for 100 hours.

[0096] Comparative Example 3

[0097] The same as Example 1, except that: step (1) uses conventional stirring instead of ultrasonic dispersion, and the shell of the catalyst finally obtained is uneven, ranging from 13 to 37 nm. The activity evaluation results of the prepared catalyst are as follows:

[0098] At a methane volume concentration of 1% and a volume space velocity of 30,000 h -1 Under the condition, T 90 The methane removal rate is 85.8% after continuous operation at 525°C for 100 hours.

[0099] At a methane volume concentration of 3% and a volume space velocity of 10000 h -1 Under the condition, T 90 The temperature is 515℃, and the methane removal efficiency is 86.2% after continuous operation at 515℃ for 100 hours.

[0100] Comparative Example 4

[0101] The same as Example 1, except that: in step (1), γ-Al2O3 is used instead of TiO2, and the catalyst is finally prepared. The activity evaluation results of the prepared catalyst are as follows:

[0102] At a methane volume concentration of 1% and a volume space velocity of 30,000 h -1 Under the condition, T 90 The methane removal rate was 85.6% after continuous operation at 545°C for 100 hours.

[0103] At a methane volume concentration of 3% and a volume space velocity of 10000 h-1 Under the condition, T 90 The temperature is 532℃, and the methane removal efficiency is 84.3% after continuous operation at 532℃ for 100 hours.

[0104] Comparative Example 5

[0105] The same as Example 1, except that: in step (1), 75% ethanol is used instead of anhydrous ethanol, and the shell thickness of the final catalyst is uneven, ranging from 12nm to 41nm. The activity evaluation results of the prepared catalyst are as follows:

[0106] At a methane volume concentration of 1% and a volume space velocity of 30,000 h -1 Under the condition, T 90 The methane removal rate was 85.1% after continuous operation at 520°C for 100 hours.

[0107] At a methane volume concentration of 3% and a volume space velocity of 10000 h -1 Under the condition, T 90 The temperature is 516℃, and the methane removal efficiency is 85.4% after continuous operation at 515℃ for 100 hours.

Claims

1. A method for preparing a methane catalytic combustion catalyst, characterized in that The method comprises the following steps: (1) ultrasonically dispersing TiO2 in anhydrous ethanol, adding hydroxysulfopropyl betaine to obtain a mixture; (2) mixing the mixture in step (1) and an active metal salt solution for reaction; (3) separating a precipitate after the reaction, and obtaining a TiO2@ABO3 core-shell catalyst through drying and calcining.

2. The method according to claim 1, characterized in that: The TiO2 described in step (1) is rutile type and has a particle size of 40 to 60 nm.

3. The method according to claim 1, characterized in that: The mass volume ratio of TiO2 to anhydrous ethanol in step (1) is 1g:10-30mL, preferably 1g:10-20mL.

4. The method according to claim 1, characterized in that: The frequency of the ultrasonic dispersion in step (1) is 2 to 4 kHz, and the ultrasonic time is 10 to 30 minutes.

5. The method according to claim 1, characterized in that: The mass ratio of hydroxysulfopropyl betaine to TiO2 added in step (1) is 1:5-20, preferably 1:10-15.

6. The method according to claim 1 or 5, characterized in that: After the hydroxysulfopropyl betaine is added in step (1), ultrasonic treatment is continued at 2 to 4 kHz for 30 to 60 minutes.

7. The method according to claim 1, characterized in that: The active metal described in step (2) is a non-precious metal, specifically including two types of metals A and B, wherein A is at least one of La and Ce, and B is at least one of Fe, Co, Ni, and Mn, wherein the molar ratio of the active metals A and B is 1:

1.

8. The method according to claim 1 or 7, characterized in that: The active metal salt solution in step (2) is a soluble metal salt, preferably one or more of nitrates and chlorides, and the concentration of the active metal salt solution is 1 to 3 mol / L.

9. The method according to claim 1, characterized in that: Step (2) adding hydroquinone to the active metal salt solution, wherein the mass concentration of hydroquinone in the solution after the addition is 3% to 5%.

10. The method according to claim 1, characterized in that: The active metal salt solution is mixed with the mixture of step (1) according to the molar ratio of TiO2 to active metal of 1:1 to 5.

11. The method according to claim 1 or 10, characterized in that: After mixing in step (2), the mixture is stirred at 40-70° C. for 1-3 hours at a stirring rate of 200-500 r / min.

12. The method according to claim 1, characterized in that: The drying temperature in step (3) is 80 to 120° C., and the drying time is 12 to 24 hours.

13. The method according to claim 1, characterized in that: The calcination temperature in step (3) is 700-800° C. and the calcination time is 4-6 hours.

14. A methane catalytic combustion catalyst, characterized in that It is prepared by the method according to any one of claims 1 to 13.

15. The catalyst according to claim 14, characterized in that: The prepared catalyst uses perovskite metal oxide ABO3 as a shell layer and TiO2 as a core, and the shell layer thickness is 5 to 35 nm.

16. Use of a methane catalytic combustion catalyst prepared by the method according to any one of claims 1 to 13 or a methane catalytic combustion catalyst according to any one of claims 14 to 15 for catalytic combustion of methane at low temperature.

17. The use according to claim 16, characterized in that: At a volume space velocity of 10000 h -1 ~30000h -1 , under the condition of methane volume concentration of 1% to 3%, T 90 ≤500℃.

Citation Information

Patent Citations

  • Perovskite type core-shell structured metal oxide and preparation method and application thereof

    CN105562122A

  • Methane low-temperature combustion catalyst for boiling-bed reactor as well as preparation method and application of methane low-temperature combustion catalyst

    CN106622276A

  • Dry reformation of methane reaction, nickel and cerium containing core-shell structured catalysts therefor and their preparation

    CN107921427A

  • Perovskite honeycomb monolithic methane catalytic combustion catalyst and preparation method thereof

    CN114870863A

  • Plate assembly for casing cooling module, assembling method for the plate assembly and assembling and repairing method for the cooling module having the plate assembly

    KR1020210014900A